2012
DOI: 10.1371/journal.pone.0035125
|View full text |Cite
|
Sign up to set email alerts
|

Artemisinin Attenuates Lipopolysaccharide-Stimulated Proinflammatory Responses by Inhibiting NF-κB Pathway in Microglia Cells

Abstract: Microglial activation plays an important role in neuroinflammation, which contributes to neuronal damage, and inhibition of microglial activation may have therapeutic benefits that could alleviate the progression of neurodegeneration. Recent studies have indicated that the antimalarial agent artemisinin has the ability to inhibit NF-κB activation. In this study, the inhibitory effects of artemisinin on the production of proinflammatory mediators were investigated in lipopolysaccharide (LPS)-stimulated primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 35 publications
6
35
0
Order By: Relevance
“…In this study, artemether has been shown to attenuate the production of NO/iNOS, PGE2/COX-2/mPGES-1, as well as the pro-inflammatory cytokines TNFα and IL-6. We therefore (2012) also showed that artemisinin inhibited IκB phosphorylation and p65 NF-κB translocation to the nucleus in LPS activated primary microglia cells [28]. It therefore appears that artemisinin derivatives, including artemether might be inhibiting LPSinduced neuroinflammation by targeting similar mechanisms involving the NF-κB signalling pathway.…”
Section: Activated Microglia Produce Various Pro-inflammatory Mediatomentioning
confidence: 88%
“…In this study, artemether has been shown to attenuate the production of NO/iNOS, PGE2/COX-2/mPGES-1, as well as the pro-inflammatory cytokines TNFα and IL-6. We therefore (2012) also showed that artemisinin inhibited IκB phosphorylation and p65 NF-κB translocation to the nucleus in LPS activated primary microglia cells [28]. It therefore appears that artemisinin derivatives, including artemether might be inhibiting LPSinduced neuroinflammation by targeting similar mechanisms involving the NF-κB signalling pathway.…”
Section: Activated Microglia Produce Various Pro-inflammatory Mediatomentioning
confidence: 88%
“…NF-κB, a pleiotropic regulator involved in microglial cell responses, can suppress the production of proinflammatory enzymes and cytokines, including NO, PGE2, TNF-α and IL-6 [13,24,34]. Under normal circumstances, NF-κB binds to IκB to form an inactive heterodimer in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in NFκB, JNK and c-Jun expression in microglia after LPS induction indicated that these pathways were involved in the LPS-induced activation. Similarly, NFκB and JNK/c-Jun pathways were demonstrated to be activated by LPS in microglia [5,6,7]. Secretion from MSC significantly reduced expression of these protein, which suggests that the reduction of proinflammatory cytokines and increase of anti-inflammatory cytokines may be mediated by these pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In response to inflammation within the CNS, microglia are activated and they assume a phenotypic shift, including changes in morphology, and producing a barrage of proinflammatory [tumor necrosis factor (TNF)-α, interleukin (IL)-6, IL-1β, nitric oxide (NO) and superoxide] and anti-inflammatory factors [IL-10, IL-13, transforming growth factor (TGF)-β)] and undergo rapid proliferation [2,3,4]. The activation of microglia has been suggested to be mediated by the NFκB and c-Jun N-terminal kinase (JNK) pathways [5,6,7]. Although, in general, microglia have a neuroprotective function, chronic activation of microglia has been implicated in the exacerbation of various neurodegenerative diseases such as Parkinson's disease, Alzheimer's disease and multiple sclerosis [2].…”
Section: Introductionmentioning
confidence: 99%